FRI0155 Α MULTICENTER "AT-RISK" COHORT FOR THE DISCOVERY OF ENVIRONMENTAL, CLINICAL AND MOLECULAR PREDICTORS FOR THE TRANSITION INTO SYSTEMIC LUPUS ERYTHEMATOSUS (SLE). (2nd June 2020) - Adamichou, C.; Nikolopoulos, D.; Nikoloudaki, M.; Rahme, Z.; Fredi, M.; Pieta, A.; Repa, A.; Parma, A.; Kalogiannaki, E.; Avgustidis, N.; Kougkas, N.; Banos, A.; et al.
Abstract : Background: SLE onset is preceded by a preclinical phase evidenced by the presence of anti-nuclear and other autoantibodies (autoAbs), which however, have low predictive value for development of clinical SLE. Objectives: To define the subgroup of autoAbs-positive individuals who are at high risk for progression into SLE by integrating environmental, clinical/serological, genetic and transcriptome data. Methods: A multicenter, across five European countries, inception cohort of autoAbs-positive individuals or first-degree relatives (FDRs) of SLE patients who are monitored prospectively over five years for possible transition to SLE according to the classification criteria. Structured data collection on demographics, family and medical history, clinical (criteria and selected non-criteria manifestations) and serological parameters, use of medications, hydroxyvitamin D levels and lifestyle (tobacco, alcohol use, physical activity, adherence to Mediterranean diet). Blood samples are stored for RNA-sequencing and genotyping. Results: A total 254 at-risk individuals (93% women, 99% Caucasians, aged [mean ± standard deviation] 36 ± 12 years) have been included and enrolment/monitoring is still ongoing. Forty individuals (16%) have FDR with SLE and 88 individuals (35%) have FDR with another autoimmune disorder. The frequency of active and past use of tobacco was 28% and 20%, respectively. Sedentary lifestyle (moving only for necessary chores or outdoor activity 1-2 times/week) was reported by 54% and adherence to the Mediterranean diet was low (3.4 ± 2.3, maximum score: 9). At enrolment, individuals had 1.9 ± 1.1 ACR-1997 classification criteria, with anti-nuclear antibodies (ANA) being the most frequent (88%), followed by synovitis (39%), photosensitivity (33%) and immunologic disorder (30%) (Table 1 ). During follow-up of 15.2 ± 7.2 months, a total 15 individuals (5.9%) have progressed into classified SLE, including cases with severe hematological and neurological disease. Conclusion: Among individuals with positive autoAbs or FDRs with SLE, the short-term risk for transition into clinical SLE is low. Following the study completion, clinical and lifestyle data will be combined with blood transcriptome to define a high-risk subgroup of individuals for progression into SLE. Acknowledgments: The study is supported by the Foundation for Research in Rheumatology (FOREUM; preclin016) Disclosure of Interests: Christina Adamichou: None declared, Dionysis Nikolopoulos: None declared, Myrto Nikoloudaki: None declared, Zahra Rahme: None declared, Micaela Fredi: None declared, Antigoni Pieta: None declared, ARGYRO REPA: None declared, Alice Parma: None declared, Eleni Kalogiannaki: None declared, Nestor Avgustidis: None declared, Nikolaos Kougkas: None declared, Aggelos Banos: None declared, Anastasios Eskitzis: None declared, Alessandra Bortoluzzi: None declared, Søren Jacobsen: None declared, Prodromos Sidiropoulos: None declared, Emmanouil Dermitzakis: None declared, Marta Mosca: None declared, Luís Inês: None declared, Laura Andreoli: None declared, Angela Tincani: None declared, Antonis Fanouriakis Paid instructor for: Paid instructor for Enorasis, Amgen, Speakers bureau: Paid speaker for Roche, Genesis Pharma, Mylan, George Bertsias Grant/research support from: GSK, Consultant of: Novartis